2019
DOI: 10.3390/medicina55080447
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathy: Pathophysiology, Therapeutic Options, and Role of Nutraceutics. A Narrative Literature Review

Abstract: Tendinopathies are very common in general population and a huge number of tendon-related procedures take place annually worldwide, with significant socio-economic repercussions. Numerous treatment options are commonly used for tendon disorders. Besides pharmacological and physical therapy, nutrition could represent an additional tool for preventing and treating this complex pathology that deserve a multidisciplinary approach. In recent years, nutraceutical products are growing up in popularity since these seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 96 publications
(99 reference statements)
0
59
0
1
Order By: Relevance
“…Some antiepileptic drugs, like pregabalin and gabapentin [ 85 ], have shown positive effects in post-traumatic neuropathic pain relief, although some side effects are reported (i.e., dizziness) and discontinuation of treatment is frequent. As in other musculoskeletal conditions [ 86 ], some multivitamin supplements and neurotrophic agents are commonly adopted, especially in neuroapraxia and axonotmesis, even if their effectiveness is debated and even if they are commonly used in sports population behind nerve injuries [ 87 ]. Perineural steroid and anesthetic injections at the site of nerve injury, commonly adopted for short relief of the pain in other several musculoskeletal conditions [ 88 ], are not routinely performed in the management of neuropathic pain but they have shown some positive results [ 89 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Some antiepileptic drugs, like pregabalin and gabapentin [ 85 ], have shown positive effects in post-traumatic neuropathic pain relief, although some side effects are reported (i.e., dizziness) and discontinuation of treatment is frequent. As in other musculoskeletal conditions [ 86 ], some multivitamin supplements and neurotrophic agents are commonly adopted, especially in neuroapraxia and axonotmesis, even if their effectiveness is debated and even if they are commonly used in sports population behind nerve injuries [ 87 ]. Perineural steroid and anesthetic injections at the site of nerve injury, commonly adopted for short relief of the pain in other several musculoskeletal conditions [ 88 ], are not routinely performed in the management of neuropathic pain but they have shown some positive results [ 89 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…It is the case of eccentric exercise for the treatment of tendinopathy (O'Neill, Watson, & Barry, 2015) (Loiacono et al, 2019), or the use of isokinetic dynamometer in the prevention of sport injuries (Croisier & Crielaard, 2001). In the last years, a novel modality of muscle contraction, iso-inertial (Tesch, Fernandez-Gonzalo, & Lundberg, 2017), is gaining more scientific interest for its potential applications.…”
Section: Practical Application To Sport Medicine and Rehabilitation Smentioning
confidence: 99%
“…These differences have impact on several functions of skeletal muscles, determining different level of tension. Recent evidences (Naugle, Naugle, Fillingim, & Riley, 2014) showed that isometric contraction could modulate pain perception (Rio et al, 2015), while eccentric contractions could have a role in the rehabilitation of muscle injuries and tendinopathies (Loiacono et al, 2019). Isometric contractions are useful to contrast hypotrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Tendon disorders are very common in sports and any anatomical district may be interested depending on the type of sport practiced (Loiacono et al, 2019). For position and role, hip and the surrounding tendons are overstressed and often overloaded, especially in athletes (Schilders et al, 2013): this could lead to the developing of several tendinopathies, among which the differential diagnosis is often complicated (Frizziero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%